2014
DOI: 10.1044/sbi15.4.125
|View full text |Cite
|
Sign up to set email alerts
|

Using the Common Core State Standards to Guide Therapy in the Schools: Confidently Accepting the Challenge

Abstract: For many school-based speech-language pathologists (SLPs), integrating the Common Core State Standards (CCSS) into therapeutic practice may seem like a daunting task. Change, however, can bring substantial opportunities for improvement and growth. This article will discuss the key changes of the CCSS and the feelings of concern of a small sample of SLPs. Implications of this research including suggestions for practitioners and SLP Leaders will be presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The existence of different types of expository discourse (e.g., compare-contrast, cause-effect) creates challenges for educators, clinicians, and researchers. Despite incorporation of expository passages in recent curricular advances (Murza et al, 2014), little is known about how the structure of a passage might influence student performance on expository comprehension and production tasks. For example, some studies have shown that students are more aware of certain expository types than others, but results have not been consistent for expository type or age/grade groupings (e.g., Cheuvront, 2002;Englert & Thomas, 1987;Richgels, McGee, Lomax, & Sheard, 1987).…”
Section: Types Of Discourse and The Curriculummentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of different types of expository discourse (e.g., compare-contrast, cause-effect) creates challenges for educators, clinicians, and researchers. Despite incorporation of expository passages in recent curricular advances (Murza et al, 2014), little is known about how the structure of a passage might influence student performance on expository comprehension and production tasks. For example, some studies have shown that students are more aware of certain expository types than others, but results have not been consistent for expository type or age/grade groupings (e.g., Cheuvront, 2002;Englert & Thomas, 1987;Richgels, McGee, Lomax, & Sheard, 1987).…”
Section: Types Of Discourse and The Curriculummentioning
confidence: 99%
“…efore the widespread adoption of the Common Core State Standards (Common Core State Standards Initiative, 2015b), narrative texts dominated the curriculum until fourth grade, with expository, or informational, textbooks and lectures becoming the primary source of teaching and learning in later grades (Snyder & Caccamise, 2010;Williams, 2005). Since the adoption of the Common Core, however, expository texts are being introduced at earlier grade levels and more frequently across all grades (Kinsella, 2013;Murza, Malani, & Hahs-Vaughn, 2014). For adolescent students in later grades, expository texts and lectures make up a predominant portion of the curriculum, especially for students who focus on coursework related to science, technology, engineering, and math (Common Core State Standards Initiative, 2015b).…”
mentioning
confidence: 99%
“…The findings suggest as experience increased, respondents were less confident in their ability to align therapy to educational standards such as the CCSS. Although the same ASHA (2010) Roles and Responsibilities document reminds SLPs that their therapy should address the linguistic and metalinguistic underpinnings of school curriculum, many SLPs are unsure of how exactly to do that (Murza, Malani, & Hahs-Vaughn, 2014). This could be due to the fact that it is a relatively newer idea in the field of speech-language pathology.…”
Section: Discussionmentioning
confidence: 99%